(untitled) (Global Journal of Management and Business Research, 2020)
Mutual fund, an investment vehicle by retail investors, is playing a vital role in our capital market by transforming the sum of the invested funds of investors into investing in a diversified portfolio by the professional investment managers. Since 1980, the mutual funds have been emerging rapidly in the stock market of Bangladesh. This research work attempts to evaluate the financial performance of growth-oriented Bangladeshi Close-end mutual funds traded in Chittagong Stock Exchange (CSE). In order to fulfill the objectives of the paper, ten mutual funds out of thirty-six have chosen. The Prime data used is the Net Asset Value (NAV) of the selected mutual funds and the returns of the CS 30 as a benchmark index. This paper concentrates on the evaluation of mutual funds by employing various research methodologies such as Treynor’s ratio, Sharpe ratio, and Jensen’s alpha and Regression Analysis. Finally, an attempt has also undertaken to assess the statistical relationship between the performance CS 30 and the mutual funds.